2017
DOI: 10.1371/journal.pone.0177217
|View full text |Cite
|
Sign up to set email alerts
|

Edema is not a reliable diagnostic sign to exclude small brain metastases

Abstract: No prior systematic study on the extent of vasogenic edema (VE) in patients with brain metastases (BM) exists. Here, we aim to determine 1) the general volumetric relationship between BM and VE, 2) a threshold diameter above which a BM shows VE, and 3) the influence of the primary tumor and location of the BM in order to improve diagnostic processes and understanding of edema formation. This single center, retrospective study includes 173 untreated patients with histologically proven BM. Semi-manual segmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Although large-sized intraparenchymal metastases of the brain mostly exhibit vasogenic edema, the presence or degree of vasogenic edema may be influenced by other factors than the lesion size, such as the primary tumor type, location of the lesion in the gray or white matter, desmoplastic effects of the chemotherapy, and the presence or absence of reactive astrogliosis around the lesion. 4,6 As the histopathological evaluation of the metastatic brain lesions in the presented case was not performed, addressing the exact cause of the absence of the peritumoral edema is not possible. A faint contrast-enhancement of the metastatic lesions, however, might be due to the lesions' poor vascularity and the signal alteration layers with T2 hypointensity and T1-FLAIR hyperintensity within the lesions might suggest the presence of relatively hypocellular fibrotic components.…”
Section: Discussionmentioning
confidence: 95%
“…Although large-sized intraparenchymal metastases of the brain mostly exhibit vasogenic edema, the presence or degree of vasogenic edema may be influenced by other factors than the lesion size, such as the primary tumor type, location of the lesion in the gray or white matter, desmoplastic effects of the chemotherapy, and the presence or absence of reactive astrogliosis around the lesion. 4,6 As the histopathological evaluation of the metastatic brain lesions in the presented case was not performed, addressing the exact cause of the absence of the peritumoral edema is not possible. A faint contrast-enhancement of the metastatic lesions, however, might be due to the lesions' poor vascularity and the signal alteration layers with T2 hypointensity and T1-FLAIR hyperintensity within the lesions might suggest the presence of relatively hypocellular fibrotic components.…”
Section: Discussionmentioning
confidence: 95%
“…This logic would have been acceptable if this phenomenon was a major drawback for FDG as a useful tracer for this purpose. Over the years, we and other groups have demonstrated that brain tumors are associated with significant edema in the surrounding white matter, which can be readily visualized by MR (83,119,120). Such edema is frequently associated with significant suppression of cortical uptake of FDG.…”
Section: Discussionmentioning
confidence: 99%
“…non-enhancing tumor margin: GBMs presented with welldefined non-enhancing tumor margin more often than BMs. Previously, brain lesions have been found to show peritumoral edema if they are larger than~9.5 mm in diameter (35). GBMs are usually large at the time of diagnosis, thus typically exhibiting extensive edema with a well-defined margin.…”
Section: Discussionmentioning
confidence: 99%